Phytonutrients in Oat (Avena sativa L.) Drink: Effect of Plant Extract on Antiradical Capacity, Nutritional Value and Sensory Characteristics - Gramza-Michałowska Anna; Kmiecik Dominik; Kobus-Cisowska Joanna; Żywica Anna; Dziedzic Krzysztof; Brzozowska Anna (Polish Journal of Food and Nutrition Sciences)
The purpose of this study was to design the formula and antioxidant potential of gluten-free oat drinks fortified with bioactive plant components. The paper describes the use of three preparations of plant origin: yellow tea leaf extract, mulberry extract and steviol glycosides from stevia leaves. Analyses of the oat drinks basic composition – including proteins, lipids, carbohydrates, dietary fiber fractions and antioxidant properties with DPPH, ABTS, ORAC and FRAP assays were conducted. Tea extract with steviosides oat drink showed the highest total phenolic concentration and the highest antioxidant activity followed by stevia and mulberry oat drink, whereas stevia oat drink showed the lowest phenolics level and weakest antioxidant activity. Moreover, the applied plant components showed moderate ability to influence the sensory values of the fortified oat drinks. The results demonstrate that tea, stevia and mulberry preparations applied in oat drinks enhanced antioxidant potential and might be a natural source of antioxidant components.